Frequency of Jaundice in Pregnancy and its Maternal and Fetal Outcome - Sahrish Kanwal, Aneela Habib, Amina Begum, Urooj Naz, Saima Ali, Sarha Kazi, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: During pregnancy, jaundice is important medical disorder more commonly seen in developing countries than developed one. Jaundice in pregnancy carries a grave for both the fetus and mother. This study is design to identify the frequency of jaundice in pregnancy and its maternal and fetal outcome to establish current local data for other health care providers. Aim: To determine the frequency of jaundice in pregnancy and its maternal and fetal outcome. Study Setting: This was a descriptive case series study conducted at the department of Obstetrics and gynecology of Civil hospital Karachi for the duration of 6 months from July 2018 to January, 2019. Subject and Methods: A total of 507 pregnant women were included in this study. The frequency of jaundice in pregnancy and its maternal and fetal outcome data was documented on pre designed proforma. Results: - The average age of the women was 25.91±4.46 years. Frequency of jaundice in pregnancy was 8.28%. Hepatic encephalopathy, disseminated intravascular coagulation, atonic PPH and maternal mortality was significantly high in those pregnant women who had jaundice. Similarly fetal outcome, still birth was 20% (20/40%) in which fresh still birth and macerated still birth was 15% and 5% which were not statistically significant while all were late neonatal death and which was significantly high in jaundice pregnant cases [45% vs. 9.7%; p=0.0005] . Conclusion: Jaundice in pregnancy is rare, but remains clinically important because of serious adverse effects on both the mother and the fetus. These disorders are complex and should be managed by experienced physicians in specialized centers.